Violence and Order in the Activities of Nepalese Shamans - Maskarinec, Gregory G. (Dhaulagiri Journal of Sociology and Anthropology, 2022)
When abuses of power are committed by those of unchallenged authority, how can justice be established? In the previous century's still-feudal society of Western Nepal, one way to seek justice was to commit ritual suicide, becoming a "vengeance suicide" that would plague the oppressor. "Vengeance suicides" are one prominent class of supernatural forces among many that shamans command as they seek to manipulate the order in the world, whether to re-establish or disrupt it. After recounting some well-known stories of these suicides, I seek to place them within the broader context of the many unseen forces that blacksmith shamans insist they can manipulate. The taxonomy of such forces I use here is a mantra that shamans recite at the beginning of any ceremony while heating his drum to improve its membrane's tension. Heating that tension is an apt metaphor for the violence seen as necessary to reorder or disorder the world, as explored here.